2013
DOI: 10.1007/s11095-013-1209-y
|View full text |Cite
|
Sign up to set email alerts
|

Electrosprayed Microparticles with Loaded pDNA-Calcium Phosphate Nanoparticles to Promote the Regeneration of Mature Blood Vessels

Abstract: Purpose The lack of control over microvasculature formation remains a key roadblock to the therapeutic vascularization and regeneration of functional tissues. In the current study, the integration of plasmid DNA (pDNA) condensation and electrospraying technologies was proposed to promote the regeneration of mature blood vessels through injectable or infusible administration of microparticles. Methods Calcium phosphate (CP) nanoparticles with encapsulated plasmids encoding vascular endothelial growth factors (p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 39 publications
0
11
0
Order By: Relevance
“…Their most recent study showed that microparticles with sequential release of PDGF and simvastatin could accelerate the dentoalveolar regeneration by enhancing osteoblastogensis and promoting bone maturation (Chang et al, 2014). In a separate study, Guo et al (2014) fabricated PLA-PEG microparticles with the loading of calcium phosphate-pDNA nanoparticles via electrospray. They found that subcutaneous infusion of microparticles with encapsulated both calcium phosphate-pVEGF and calcium phosphate-pbFGF nanoparticles can significantly increase the densities of blood vessels and induce a rapid maturation of blood vessels with marginal probability of cytotoxicity and inflammatory response.…”
Section: Applicationsmentioning
confidence: 99%
“…Their most recent study showed that microparticles with sequential release of PDGF and simvastatin could accelerate the dentoalveolar regeneration by enhancing osteoblastogensis and promoting bone maturation (Chang et al, 2014). In a separate study, Guo et al (2014) fabricated PLA-PEG microparticles with the loading of calcium phosphate-pDNA nanoparticles via electrospray. They found that subcutaneous infusion of microparticles with encapsulated both calcium phosphate-pVEGF and calcium phosphate-pbFGF nanoparticles can significantly increase the densities of blood vessels and induce a rapid maturation of blood vessels with marginal probability of cytotoxicity and inflammatory response.…”
Section: Applicationsmentioning
confidence: 99%
“…One part of a tissue sample was frozen and cut into sections for histopathological examinations by hematoxylin‐eosin (HE) staining and for collagen identification by Masson's trichrome staining (BBC Biochemical, Stanwood, WA) . Another part of the tissue was fixed in formalin, paraffin‐embedded, and sectioned for immunohistochemical staining of α‐SMA as described previously . Briefly, tissue sections were incubated with 3% H 2 O 2 to inactivate endogenous peroxidase, followed by an exposure to microwave heating in 10 × 10 −3 m citrate buffer solution (pH 6.0) to recover antigens.…”
Section: Methodsmentioning
confidence: 99%
“…The microdroplets (and the nanoemulsion included in them) were hardened by UVinduced polymerization of the corresponding monomers. Guo et al, (2014) [25] prepared calcium phosphate nanoparticles loaded with a plasmid encoding two growth factors. The nanoparticles were included in microparticles prepared by electrospray using a mixture of poly(ethylene glycol) (PEG) blended with the copolymer poly(ethylene glycol)-poly(Lactide) (PELA).…”
Section: Emulsion Techniquesmentioning
confidence: 99%
“…Further treatment consisting on dissolving gelatin by using proteases and subsequent fluorescent quantitation assays were performed to determine the amount of plasmid DNA initially loaded in the trojan microparticles [17]. In the same sense, Guo et al, (2014) [25] dissolved the PEG-PELA trojan microparticles in methylene chloride. The calcium phosphate nanoparticles included in them were extracted several times in aqueous media.…”
Section: Active Compound Encapsulation Efficiency In Trojan Micropartmentioning
confidence: 99%